2017
DOI: 10.1111/joic.12399
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic ointment only (lidocaine/prilocaine) instead of injectable local lidocaine in trans‐radial catheterization: A viable no‐needle alternative

Abstract: Pain levels measured by VAS were found to be similar between the two groups during sheath insertion (VAS: AO: 4.84 ± 1.0 vs 4.82 ± 1.2, P = NS), as well as 30 min after sheath removal (VAS: AO: 0.07 ± 0.5 vs LA: 0.15 ± 0.6, P = NS). The time to obtain radial access was also not affected by the use of anesthetic ointment (AO: 62.24 ± 25.7 s vs LA: 64.04 ± 18.78 sec, P = NS). The rate of clinical or angiographic radial artery spasm was similar (8-10%) between the groups (P = NS) CONCLUSION: Use of a local anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Other anesthetics without needles have been studied such as lidocaine/prilocaine mixture presented as an ointment which have been shown as an alternative of lidocaine infiltration in transradial cardiac catheterization [ 20 ]. However, this anesthetic has never been compared with the 50% nitrous oxide/oxygen premix (Kalinox).…”
Section: Discussionmentioning
confidence: 99%
“…Other anesthetics without needles have been studied such as lidocaine/prilocaine mixture presented as an ointment which have been shown as an alternative of lidocaine infiltration in transradial cardiac catheterization [ 20 ]. However, this anesthetic has never been compared with the 50% nitrous oxide/oxygen premix (Kalinox).…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were conducted in 17 countries: 10 in Spain ( Giner et al, 1996, Giner et al, 2000, Guevara Sanz and Conde Anguita, 2001, Guevara Sanz and Requena Castillo, 2011, seven in France ( Bobbia et al, 2013, seven in the United Kingdom ( Lightowler and Elliott, 1997, three in Iran ( Bastami et al, 2015, two in Turkey ( Baskın et al, 2014, two in the United States ( Matheson et al, 2014, two in Australia ( Tran et al, 2002, one in Canada ( Aaron et al, 2003 ), one in Mexico ( Cortés-Télles et al, 2012 ), one in Singapore ( Ibrahim et al, 2015 ), one in Egypt , one in South Korea, ( Kim et al, 2007 ) one in Greece ( Latsios et al, 2017 ), one in India ( Mahto et al, 2016 ), one in Italy ( Pagnucci et al, 2020 ), one in Austria ( Ruetzler et al, 2012 ), and one in Germany ( Rüsch et al, 2017 ) ( Table 1 ). Five of the studies were published before 20 0 0 ( Lightowler and Elliott, 1997, 16 between 20 0 0 and 2010 ( Matheson et al, 2014, Giner et al, 20 0 0 , Joly et al, 1998, Guevara Sanz and Conde Anguita, 2001, Micu et al, 20 06 , L'Her et al, 20 01 , France et al, 20 08 , Grandpierre et al, 2019, and 22 after 2010 ( Bobbia et al, 2013, Rüsch et al, 2017, Guevara Sanz and Requena Castillo, 2011.…”
Section: Characteristics Of Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…Ten ( Joly et al, 1998, Rüsch et al, 2017 studies explored pain due to arterial catheterization; the others investigated pain due to blood collection for arterial blood gas analysis. When arterial catheterization was performed, a needle gage of 17.5 ( Russell et al, 1988 ), 18 ( Joly et al, 1998 ), or 20 ( Kim et al, 2007;Latsios et al, 2017;Olday et al, 2002;Ruetzler et al, 2012;Rüsch et al, 2017;Sherwin et al, 2003;Smith et al, 1990;Tatlı et al, 2018 ) was employed. Blood collection for arterial blood gas analysis was performed using a needle gage of 22 ( Giner et al, 1996, Guevara Sanz and Requena Castillo, 2011, 23 ( Patout et al, 2015, 25 ( Patout et al, 2015, Guevara Sanz and Requena Castillo, 2011 26, ( Micu et al, 2006), 27 ( Cortés-Télles et al, 2012, and 29 ( Hajiseyedjavady et al, 2012;Ibrahim et al, 2015;Lightowler and Elliott, 1997 ).…”
Section: Arterial Puncture Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1988 Goodacre et al showed that LPC, from the EMLA brand, could be as effective as infiltrative anesthesia in reducing pain for skin grafting (9). Previous research findings had noted the efficacy of LPC compared to IL in transradial catheterization (10), perineal tears following vaginal delivery (11,12), and some pediatric procedures like lumbar punctures and venipunctures (13,14). Additionally, LPC can be substituted for infiltrative prilocaine in pediatric femoral catheterization (15).…”
Section: Introductionmentioning
confidence: 99%